Membangun Compound Brand Image dan Media Sosial dalam Mempengaruhi Keputusan Mahasiswa Memilih Universitas Muhammadiyah Aceh - Erlinda, Erlinda; Sulfitra, Sulfitra; Nuzulman, Nuzulman (Universitas muhammadiyah palembang, 2024)
The purpose of this research is to examine the effect of compound brand image and social media to students decision (case study on University o Muhammadiyah Aceh students). This study applies causality-explanatory approach, with primary data in thr form of 217 students perception as individual research object. The method of data collection is survey using questionaire. To analyze the data is used Partial Least Square with second order. The result indicate that compound brand image and social media have significant effect to student decision choosing Universitas Muhammadiyah Aceh. Compound brand image has a greater effect than social media, in influencing students decision to choose Universitas Muhammadiyah Aceh.